1987
DOI: 10.1002/j.1460-2075.1987.tb04714.x
|View full text |Cite
|
Sign up to set email alerts
|

The cytochrome oxidase subunit I and subunit III genes in Oenothera mitochondria are transcribed from identical promoter sequences

Abstract: Two loci encoding subunit III of the cytochrome oxidase (COX) in Oenothera mitochondria have been identified from a cDNA library of mitochondrial transcripts. A 657‐bp sequence block upstream from the open reading frame is also present in the two copies of the COX subunit I gene and is presumably involved in homologous sequence rearrangement. The proximal points of sequence rearrangements are located 3 bp upstream from the COX I and 1139 bp upstream from the COX III initiation codons. The 5′‐termini of both CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…Two primers were designed corresponding to two regions of the cytochrome oxidase subunit III gene (coxIII) that are conserved between angiosperms and the moss Physcomitrella (15,19,20). The first nucleotides of the primers 5'-GTAGATCCAAGTCCATG-GCCT-3' and 5'-GCATGATGGGCCCAAGTTACGGC-3' align with nt 34 and 458, respectively, ofthe Oenothera coxIll sequence (20). The intervening sequence fragments were amplified from total DNA preparations and from first-strand cDNA, respectively, with 30 cycles of 1 min at 94°C, 2 min at 60°C, and 4 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…Two primers were designed corresponding to two regions of the cytochrome oxidase subunit III gene (coxIII) that are conserved between angiosperms and the moss Physcomitrella (15,19,20). The first nucleotides of the primers 5'-GTAGATCCAAGTCCATG-GCCT-3' and 5'-GCATGATGGGCCCAAGTTACGGC-3' align with nt 34 and 458, respectively, ofthe Oenothera coxIll sequence (20). The intervening sequence fragments were amplified from total DNA preparations and from first-strand cDNA, respectively, with 30 cycles of 1 min at 94°C, 2 min at 60°C, and 4 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…Position 102 represents another example of the alteration that modifies a genomic arginine triplet CGG to UGG, where tryptophan is conserved in nonplant species polypeptides (Table II), as well as in monocot plants. A genomic TGG has been found in fact at the same position in the wheat (9), maize (15), rice (12) mitochondrial genomic sequences, whereas a genomic CGG codon is found at the same position in all the dicot coxIII genes analyzed so far (6,10,13). Editing at position 102, which does occur in sunflower, is probably also required in the other dicots coxIII mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Fractions 9 through 15 represent the major protein peak and from the polypeptide compositions of the individual fractions it was evident that this was a composite peak of two major overlapping groups of polypeptides. The measured Cyt c oxidation activity suggested that it was only the first of these peaks (fractions [9][10][11][12] The visible absorption spectra of the air oxidized and the dithionite-reduced enzyme are shown in Figure 3. The characteristic a-band of Cyt c oxidase at 600 nm was clearly visible in the reduced spectrum and allowed the calculation of a haem content of 7 nm mg-' for the enzyme as eluted from the Mono Q column.…”
Section: Silver Staining Of Gelsmentioning
confidence: 99%
“…Polypeptides that copurify with the maize Cyt c oxidase enzyme activity have been compared directly with a yeast Cyt c oxidase preparation, and the cross-reactivities of a number of antibodies prepared against yeast and sweet potato Cyt c oxidase subunits were assessed. Information on the polypeptide structure of maize Cyt c oxidase will complement our knowledge ofthe structure and sequence ofthe corresponding genes which have been isolated, predominantly from maize, in this laboratory and others (7,10,11,19). The availability of both gene and antibody probes for the components of Cyt c oxidase will allow a detailed analysis of the regulation of expression of this important enzyme during plant development.…”
mentioning
confidence: 93%
See 1 more Smart Citation